Pretreatment evaluation of fluorescence resonance energy transfer‐based drug sensitivity test for patients with chronic myelogenous leukemia treated with dasatinib. Issue 7 (29th May 2018) - Kondo, Takeshi; Fujioka, Mari; Tsuda, Masumi; Murai, Kazunori; Yamaguchi, Kohei; Miyagishima, Takuto; Shindo, Motohiro; Nagashima, Takahiro; Wakasa, Kentaro; Fujimoto, Nozomu; Yamamoto, Satoshi; Yonezumi, Masakatsu; et al.
Abstract : Tyrosine kinase inhibitors (TKI) are used for primary therapy in patients with newly diagnosed CML. However, a reliable method for optimal selection of a TKI from the viewpoint of drug sensitivity of CML cells has not been established. We have developed a FRET‐based drug sensitivity test in which a CrkL‐derived fluorescent biosensor efficiently quantifies the kinase activity of BCR‐ABL of living cells and sensitively evaluates the inhibitory activity of a TKI against BCR‐ABL. Here, we validated the utility of the FRET‐based drug sensitivity test carried out at diagnosis for predicting the molecular efficacy. Sixty‐two patients with newly diagnosed chronic phase CML were enrolled in this study and treated with dasatinib. Bone marrow cells at diagnosis were subjected to FRET analysis. The ΔFRET value was calculated by subtraction of FRET efficiency in the presence of dasatinib from that in the absence of dasatinib. Treatment response was evaluated every 3 months by the BCR‐ABL1 International Scale. Based on the ΔFRET value and molecular response, a threshold of the ΔFRET value in the top 10% of FRET efficiency was set to 0.31. Patients with ΔFRET value ≥0.31 had significantly superior molecular responses (MMR at 6 and 9 months and both MR4 and MR4.5 at 6, 9, and 12 months) compared with the responses in patients with ΔFRET value <0.31. These results suggest that the FRET‐based drug sensitivity test at diagnosis can predict early and deep molecular responses. This study is registered with UMIN Clinical Trials Registry (UMIN000006358). Abstract : Patients with CML are effectively stratified by combination of FRET‐based drug sensitivity test and halving time.